Angiographic features after photodynamic therapy for choroidal neovascularisation in age related macular degeneration and pathological myopia. Issue 2 (1st February 2003) - Parodi, M B; Da Pozzo, S; Ravalico, G
Abstract : Aim: To describe the angiographic features after photodynamic therapy (PDT) with verteporfin in choroidal neovascularisation (CNV) associated both with age related macular degeneration (AMD) and pathological myopia (PM). Methods: 36 patients affected by subfoveal CNV in AMD and 25 patients with subfoveal CNV in PM underwent an ophthalmological examination including fluorescein angiography (FA) and indocyanine green angiography (ICGA) using the IMAGEnet System. Post-PDT examinations were performed 7, 30, and 90 days later. Results: The typical angiographic aspect after PDT for AMD related CNV was a round hypofluorescence visible both on FA and on ICGA, which included both CNV and the surrounding tissues and corresponded to the area exposed to laser light. In PM the CNV appeared hypofluorescent during the early phases and gradually became hyperfluorescent during the late phases on FA, whereas on ICGA it was detectable in its whole extension as a hyperfluorescent lesion since the early phases. Differently from AMD, there was no round hypofluorescence surrounding the CNV on FA or on ICGA. Moreover, five patients in the AMD group showed hot spots on ICGA, which spontaneously disappeared during the follow up. Classic and occult components of the AMD related CNV revealed a different angiographic response to PDT, showing with the latter only a partial closure 1 week after PDT followed by a complete reopening at the first month in 100% of cases. Conclusion: The post-PDT hypofluorescence typical of AMD related CNV, especially visible on FA, might be secondary to a combination of choriocapillary occlusion and masking effect due to swelling of retinal pigment epithelium cells. Hot spots in the AMD affected patients could be interpreted as the expression of a non-thermal choroidal vasculitis secondary to PDT.